Disentangling Accretion Disk and Dust Emissions in the Infrared Spectrum of Type 1 AGN - Hernán-Caballero, Antonio; Hatziminaoglou, Evanthia; Alonso-Herrero, Almudena; Mateos, Silvia (Frontiers in Astronomy and Space Sciences, 2017)
We use a semi-empirical model to reproduce the 0.1–10μm spectral energy distribution (SED) of a sample of 85 luminous quasars. In the model, the continuum emission from the accretion disk as well as the nebular lines are represented by a single empirical template (disk), where differences in the optical spectral index are reproduced by varying the amount of extinction. The near- and mid-infrared emission of the AGN-heated dust is modelled as the combination of two black-bodies (dust). The model fitting shows that the disk and dust components are remarkably uniform among individual quasars, with differences in the observed SED largely accounted for by varying levels of obscuration in the disk as well as differences in the relative luminosity of the disk and dust components. By combining the disk-subtracted SEDs of the 85 quasars, we generate a template for the 1–10μm emission of the AGN-heated dust. Additionally, we use a sample of local Seyfert 1 galaxies with full spectroscopic coverage in the 0.37μm to 39μm range to demonstrate a method for stitching together spectral segments obtained with different PSF and extraction apertures. We show that the disk and dust templates obtained from luminous quasars also reproduce the optical-to-mid-infrared spectra of local Seyfert 1s when the contribution from the host galaxy is properly subtracted.